Measurement-based multicast admission control in DiffServ networks - Alanen, O.; Paakkonen, M.; Hamalainen, T.; Ketola, M.; Joutsensalo, J. (The 7th International Conference on Advanced Communication Technology, 2005, ICACT 2005, 2005)
Multicast admission control in differentiated services network is an important but lightly researched subject. We propose two distinct admission control methods. The methods reject new multicast join requests that would otherwise decrease the quality experienced by the existing receivers. Edge nodes filter join requests and generate new requests. The proposed methods are developed as an extension to the DSMCast protocol but could also be adapted to other protocols. In this paper the methods are compared against each other and to the situation without any admission control